Otolith Shape Analysis and Otolith Morphometry of Bogue Boops boops (Linnaeus, 1758) in the Aegean Sea and the Marmara Sea - Yusuf Şen; İsmail Burak Daban; Mukadder Arslan İhsanoğlu; Oğuzhan Ayaz; Uğur Özekinci (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries, 2025)
In the present study, otolith shape indices and some otolith morphometric characteristics in the left and right sagittal otoliths were identified and compared for Boops boops in the Aegean Sea and the Marmara Sea. Otoliths of Boops boops from 244 individuals in the North of Aegean Sea and 188 individuals from the Southwest of Marmara Sea were analyzed during the 2024 fishing season. The total length-otolith dimensions relationships were evaluated, the best fit was obtained between total length and otolith perimeter in the Marmara Sea and Aegean Sea, while the least fit was obtained among total length and otolith area of right otoliths, total length and otolith length of left otoliths in the Aegean Sea and Marmara Sea. Some similarities of Boops boops stocks were found with shape indices and otolith morphometry between the Aegean Sea and Marmara Sea. The otolith area and circularity of the left otolith, roundness and rectangularity of the right otolith, form factor of left and right otolith were significantly different (p<0.05). Principle Component Analysis may explain these differences as arising from variations in the roundness, otolith area and otolith width. Also, Canonical Discriminant Analysis demonstrated significant discrimination of otoliths between the Aegean Sea and the Marmara Sea (p<0.05), and 56.6% of the originally grouped cases were correctly classified. Based on the results of this study, two stocks of Boops boops in the North of Aegean Sea and the Southwest of Marmara Sea might be different. Howewer, more detailed studies are required the determine whether this species constitues the same stock in these areas.